A novel nanofiber microfiltration membrane: Fabrication and characterization of tubular electrospun nanofiber (TuEN) membrane - Aslan, Taha; Arslan, Serkan; Eyvaz, Murat; Guclu, Serkan; Yüksel, Ebubekir; Koyuncu, Ismail (Elsevier, 2016)
Nanofibers fabricated with electrospinning method have several prominent properties such as high specific surface area, high porosity and uniform pore size distribution in nanoscale or microscale. These unique features are vital for separation processes in water and wastewater treatment applications. In this study, we have developed a new type of nanofiber electrospun membrane for the first time by collecting nanofibers on a hollow braided rope. The nanofiber membranes were characterized with Scanning Electron Microscope images, pore size, contact angle and porosity measurements. Filtration performances of tubular nanofiber and a commercial hollow braided reinforced membrane were determined for both standard particle solutions and surface water under low vacuum pressures. The novel tubular nanofiber (TuEN) membranes exhibited high water fluxes in even low vacuum pressures, relatively high removal efficiencies of turbidity (95%), total organic carbon (29%) and UV254 (45%) compared to other microfiltration membranes. We claim that the tubular nanofiber membrane will attract more attention in coming years in the fields of water and wastewater treatment. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Electrospinning; Tubular nanofiber; PAN; Hydrophilicity